Pelatihan Pembuatan Alat Praktikum pada Materi Pemisahan Campuran bagi Guru-Guru IPA di SMP - Fadiawati, Noor; Diawati, Chansyanah; Herlina, Kartini; Priadi, Median Agus (Universitas Lampung, 2024)
Practicums or experiments in laboratories are one of the main characteristics of Natural Sciences (IPA) learning in junior high schools, as a process of gaining knowledge and skills that students should experience. However, practical activities in schools often cannot be carried out, due to unavailability of equipment. One of the materials that basically requires students to do practical work is the material on separating mixtures. The aim of this activity is: to increase the knowledge and creativity of science teachers in creating/modifying practical tools. The methods used are lectures, discussions and practice testing tools. The target of this activity is 30 science teachers in junior high schools who are members of the Metro City Science Subject Teachers' Conference. The data collection technique in this activity uses a pretest and is then analyzed by calculating N-Gain. The results of the activities that have been carried out show an increase in teachers' understanding of mixture separation material, as indicated by the average n-gain between pretest and posttest of 0.73; increasing teacher insight regarding making practical tools, increasing teacher skills in designing practical tools. In addition, the average teacher satisfaction with the training activities carried out was 93% (very good category). Based on these results, it can be concluded that training activities are effective in increasing teachers' understanding and creativity in modifying practical tools.Keywords: practical tools; separation of mixtures; teacher training AbstrakPraktikum atau percobaan di laboratorium merupakan salah satu karakteristik utama pada pembelajaran Ilmu Pengetahuan Alam (IPA) di SMP, sebagai suatu proses untuk mendapatkan pengetahuan, dan keterampilan yang seyogyanya dialami oleh siswa. Akan tetapi, kegiatan praktikum di sekolah sering kali tidak dapat dilakukan, karena tidak tersedianya alat. Salah satu materi yang dasarnya mengharuskan siswa melakukan praktikum adalah materi pemisahan campuran. Tujuan dari kegiatan ini adalah: meningkatkan pengetahuan dan kreativitas guru IPA dalam membuat/memodifikasi alat praktikum. Metode yang digunakan adalah ceramah, diskusi, dan praktik uji coba alat. Sasaran dari kegiatan ini adalah guru-guru IPA yang berjumlah 30 orang di SMP yang tergabung dalam Musyawarah Guru Mata Pelajaran IPA Kota Metro. Teknik pengambilan data dalam kegiatan ini menggunakan pretest dan yang kemudian di analisis dengan menghitung N-Gain. Hasil dari kegiatan yang telah dilakukan menunjukkan adanya peningkatan pemahaman guru tentang materi pemisahan campuran, yang ditunjukkan dengan n-gain rata-rata antara pretest dan postest sebesar 0,73; meningkatnya wawasan guru terkait pembuatan alat praktikum, meningkatnya keterampilan guru dalam mendesain alat praktikum. Di samping itu, diperoleh rata-rata kepuasan guru terhadap kegiatan pelatihan yang dilaksanakan sebesar 93% (kategori sangat baik). Berdasarkan hasil tersebut, dapat disimpulkan bahwa kegiatan pelatihan efektif dalam meningkatkan pemahaman dan kreativitas guru dalam memodifikasi alat praktikum.Kata Kunci: alat praktikum; pelatihan guru; pemisahan campuran